Evaluation of Chlamydia Pneumoniae IgG in a Sample of Rheumatoid Arthritis Patients - Salloom, Dunya; Abdul Amir, Sameer; Abbas, Ali (Iraqi Journal of Science, 2023)
Thirty serum samples of patients suffering from rheumatoid arthritis after screening of rheumatoid factor, C-reactive protein and ESR were collected and including in present study to detect the IgG antibody against Chlamydia pneumoniae by ELISA test. The results showed only 2(6%) patients had seropositive of C. pneumoniae, this lead to suggest that C. pneumoniae may be one of the etiological or trigger factor in patients of rheumatoid arthritis.